2019
DOI: 10.1002/jpln.201800435
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitrogen supplementation in alleviating drought‐associated growth and metabolic impairments in Phoebe zhennan seedlings

Abstract: Drought is one of the major environmental stresses altering forest productivity. However, nutrient availability can modulate drought resistance. Phoebe zhennan (gold Phoebe) is a high‐quality timber‐producing but threatened tree species in China, facing serious anthropogenic disturbances and abiotic constraints that restrict its growth and development. However, little attention has been given to designing adaptive strategies for its management by evaluating the possible role of major nutrients, particularly ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 63 publications
4
13
0
Order By: Relevance
“…Our study also reached a similar conclusion; specifically, under drought stress, the plant height, stem diameter, total biomass and biomass accumulation of roots, stems and leaves of R. pseudoacacia seedlings decreased, indicating the response of plants to drought stress. Other studies have shown that the inhibition of growth caused by drought stress can be compensated by increasing N application, which is shown to promote root development, enhance plant water absorption capacity, promote plant dry matter accumulation, and enhance plant tolerance to drought stress ( Shi et al., 2017; Ding et al., 2018; Tariq et al., 2019). In our study, nitrogen treatment effectively slowed the inhibitory effect of drought on growth, and the morphological parameters of the MN treatment were higher than those of the HN treatment, which indicates that excessive application of N under drought conditions can inhibit the growth of plants, which is consistent with previous studies ( Yin et al., 2010; Shi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Our study also reached a similar conclusion; specifically, under drought stress, the plant height, stem diameter, total biomass and biomass accumulation of roots, stems and leaves of R. pseudoacacia seedlings decreased, indicating the response of plants to drought stress. Other studies have shown that the inhibition of growth caused by drought stress can be compensated by increasing N application, which is shown to promote root development, enhance plant water absorption capacity, promote plant dry matter accumulation, and enhance plant tolerance to drought stress ( Shi et al., 2017; Ding et al., 2018; Tariq et al., 2019). In our study, nitrogen treatment effectively slowed the inhibitory effect of drought on growth, and the morphological parameters of the MN treatment were higher than those of the HN treatment, which indicates that excessive application of N under drought conditions can inhibit the growth of plants, which is consistent with previous studies ( Yin et al., 2010; Shi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…In N-limiting ecosystems, high soil N availability after the addition of N could improve net primary production and alter stoichiometric homeostasis, which might shift such ecosystems towards phosphorus (P) limitation (Crowley et al 2012). Thus, relative changes in N and P may result in a series of modifications to plant performance, as has been widely observed in terms of biomass allocation among organs, photosynthesis, osmotic adjustment and morphological plasticity (Poorter et al 2012;Sun et al 2018;Tariq et al 2019;Yang et al 2014). Nevertheless, water deficit limits the mobility of nutrient elements in dehydrated soils, uptake by roots and vertical migration to leaves, generating asymmetric divergences in nutrient concentrations and allocation among different tissues (Gonzalez-dugo et al 2012;Kou et al 2018;Yuan & Chen 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, choose the appropriate nitrogen concentration may results in enhanced drought resistance of plants 23 . However, the response to nitrogen and water supply depend on plant species as found in Phoebe zhennan where nitrogen fertilization plays a crucial role in alleviating water stress damage 24 . The amount of CO 2 in the sub-stomatal cavity depends on the g s and on the mesophyll conductance from sub-stomatal cavities into the chloroplasts and by metabolic processes.…”
Section: Resultsmentioning
confidence: 99%